Quantifying the sociality of wild tool-using New Caledonian crows through an animal-borne technology - Burns, ZT (2014)
New Caledonian crows (NC crows; Corvus moneduloides) are the most prolific avian tool-users and crafters, using up to three unique tool types derived from numerous plant materials. Since the discovery that wild populations of NC crows use and manufacture different tools in different locations with no measured environmental correlates to these distributions, the process by which NC crows acquire their tool-oriented behavior has been investigated. Two major findings were discovered in 2005: NC crows have a genetic predisposition to manipulate stick like objects, and they increase their rate of manipulation when exposed to social influences. Since then, much of the research into the sociality of wild NC crows has focused on direct social influences, especially the parent-juvenile relationship, yet no social network of wild NC crows has been described. In my thesis, I characterized a new proximity-logging device, Encounternet, and outline a four-step plan to assess error in animal borne devices; uncovered drivers, such as relatedness, space-use, and environmental factors, of wild NC crow sociality, and experimentally manipulated the social network, revealing immediate changes to the number of day-time and roosting partners, the breakdown of first-order relatedness driving sociality, and an increase in the amount of time NC crows associate; and revealed an indirect pathway via tools left behind by conspecifics allowing for the transmission of tool-properties between unrelated NC crows. Altogether, I furthered our understanding of wild NC crow sociality through the use of an animal-borne device, experimental manipulation in the wild measuring the response of the NC crow social network, and demonstrated the utility of animal-borne devices in mapping the network of a population of wild birds.